Feral: Re-wilding the Urban Child through Process Driven Design and an Appreciation of Weeds - Rennie, Kathryn (School of Architecture, Planning and Geomatics, 2021)
Due to our rapidly urbanising population, the number of children that have little or no access to nature is increasing. Interactions with nature not only improve the mental and physical development but also foster a consciousness and enchantment with the natural world. As naturalness, proximity, scale, and modifiability of spaces are key aspects that determine the pleasure that children experience in public spaces, neighbourhood parks will become increasingly important part of the urban fabric. The funding model for public open space provisions in South Africa preferences initial capital outlay over maintenance over time. This leads to the creation of parks that decline over time and become unappealing and dangerous to residents of the area. Small-scale neighbourhood parks are the first to feel the effects when there is a reduction in public spending. This project intends to create a new model that requires a paradigm shift from the current funding model to one that assigns funding primarily to a management strategy that allows for continued management and design intervention over the lifetime of the park. There is great potential for these parks to become resilient and heuristic spaces where children can immerse themselves in natural processes and learn to appreciate urban ecology through interaction and play. By acknowledging that landscapes are open systems and by utilising the processes and life forms that thrive in the city, such as weeds, the designer can work with the energy of nature and society to create adaptive spaces that are appealing to children. The benefits of this method are two-fold. Firstly, using plants that are free and prolific allows children to have unprescribed and tactile interactions with nature, and secondly, it will increase the biodiversity of the city by valuing novel ecosystems and harnessing ecological processes. The design is dynamic and flexible made up of primarily catalytic interventions that both expose and accelerate natural processes on site, as well as proposed design responses to the predicted outcomes of these processes. In this way, the designers input acts as a scaffold for natural systems to develop rather than any predetermined outcome. The process of design is never complete, there is no maintaining of a single state. It is a design that is on-going and that adapts to social and environmental change so that it evolves with the guiding hand of the designer. By utilising this method in the design of a public open space in Woodstock, this dissertation tests a new model for designing small scale urban parks that could be replicated throughout the Cape Town Metropolitan Area. Neighbourhood parks and other undervalued public spaces can become places where humans and nature can come together and have meaningful interactions